AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE SONG LYRICS BY JAMIE MILLER - Alvinorius Datul; I Gusti Ayu Mahatma Agung (British (Jurnal Bahasa dan Sastra Inggris), 2023)
Figurative language is the use of terms or phrases that have a distorted meaning. Figurative language produces images in readers’ minds and expresses ideas in new, clear, and creative ways. Moreover, figurative language is a part of literature. A significant impression or experience is conveyed through the use of an interesting or creative contrast in literature. This research aims to identify the different kinds of figurative language used in Jamie Miller’s song lyrics. The data was collected by reading the scripts, listening to the songs, analyzing and categorizing the lyrics, and noticing the use of figurative language. The data were descriptively evaluated by the authors using a qualitative approach. Fifteen data of figurative language are found in Jamie Miller’s song lyrics. The results show that there are four types of figurative language used in Jamie Miller’s song lyrics: personification (three), metaphor (two), simile (one), and hyperbole (nine). Hyperbole is the most dominant type of figurative language used in Jamie Miller’s song lyrics.